Republished review: Next generation sequencing for clinical diagnostics and personalised medicine: implications for the next generation cardiologist. Issue 1038 (22nd March 2012) - Ware, James S; Roberts, Angharad M; Cook, Stuart A
Abstract : The fast moving field of genomic medicine is already impacting on clinical care and cardiologists are fortunate to be in a position to benefit early from the transformative advances in genomics. However, the challenges associated with genomics in the clinic in general, and with next generation sequencing technologies in particular, are significant and cardiologists need to be prepared if they wish to surf the wave of genomic opportunity. This paper presents an overview of the implications of next generation sequencing for clinical diagnostics and personalised medicine in the cardiology clinic.